Progress in China's Unconventional Oil & Gas Exploration and Development and Theoretical Technologies - Caineng, ZOU; Zhi, YANG; Rukai, ZHU; Guosheng, ZHANG; Lianhua, HOU; Songtao, WU; Shizhen, TAO; Xuanjun, YUAN; Dazhong, DONG; Yuman, WANG; Lan, WANG; Jinliang, HUANG; et al. (Acta geologica Sinica (Beijing), 2015)
The new century has witnessed a strategic breakthrough in unconventional oil & gas. Hydrocarbon accumulated in micro‐/nano‐scale pore throat shale systems has become an important domain that could replace current oil & gas resources. Unconventional oil & gas plays an increasingly important role in our energy demand. Tight gas, CBM, heavy oil and asphaltic sand have served as a key domain of exploration & development, with tight oil becoming a ‘bright spot’ domain and shale gas becoming a ‘hotspot’ domain. China has made great breakthroughs in unconventional oil & gas resources, such as tight gas, shale gas, tight oil and CBM, and great progress in oil shale, gas hydrate, heavy oil and oil sand. China has an estimated (223–263)×108t of unconventional oil resources and (890–1260)×1012 m3 of gas resources. China has made a breakthrough for progress in unconventional oil & gas study. New progress achieved in fine‐grained sedimentary studies related to continental open lacustrine basin large‐scale shallow‐water delta sand bodies, lacustrine basin central sandy clastic flow sediments and marine‐continental fine‐grained sediments provide a theoretical basis for the formation and distribution of basin central reservoir bodies. Great breakthroughs have been made in unconventional reservoir geology in respect of research methodology & technology, multi‐scale data merging and physical simulation of formation conditions. Overall characterization of unconventional reservoirs via multi‐method and multi‐scale becomes increasingly popular and facilitates the rapid development of unconventional oil & gas geological theory, method and technology. The formation of innovative, continuous hydrocarbon accumulation theory, the establishment of the framework of the unconventional oil & gas geological theory system, and the determination of the implications, geological feature, formation mechanism, distribution rule and core technology of unconventional oil & gas geological study lays a theoretical foundation for extensive unconventional oil & gas exploration and development. Theories and technologies of unconventional oil & gas exploration and development developed rapidly, including some key evaluation techniques such as ‘sweet spot zone’ integrated evaluation and a six‐property evaluation technique that uses hydrocarbon source, lithology, physical property, brittleness, hydrocarbon potential and stress anisotropy, and some key development & engineering technologies including micro‐seismic monitoring, horizontal drilling & completion and “factory‐like” operation pattern, “man‐made reservoir” development, which have facilitated the innovative development of unconventional oil & gas. These breakthroughs define a new understanding in four aspects: ① theoretical innovation; ② key technologies; ③ complete market mechanism and national policy support; and ④ well‐developed ground infrastructure, which are significant for prolonging the life cycle of petroleum industry, accelerating the upgrade and development of theories and technologies and altering the global traditional energy structure.